Культурно-просвітницька діяльність білоруських національних організацій на території України в 1918 р. - Панасюк, Олександр; Panasyuk, Oleksandr (My University, 2016)
У статті здійснено спробу проаналізувати основні напрями культурно-просвітницької діяльності білоруських національних організацій у Києві та Одесі. Окреслено головні засоби популяризації білоруської культури серед білорусів, звернуто увагу на значення просвітницької роботи в білоруському державотворчому процесі.The article is an attempt to analyze the main principles of the Belarusian national groups in Ukraine. Attention is paid to cultural and educational activities of the Belarusian National Societies in Kiev and Odessa. The basic tools popularize Belarusian culture among soldiers and Belarusian refugees living in Ukraine. There are stated the preconditions for the creation of «Belarusian national organization in Ukraine», defined purpose and its main task. The value of weekly magazine «Belorusskoe echo» is analyzed in the educational work of the Society. A separate analysis is made of cultural and educational activities of the Belarusian society «Gay» in Odessa.
Cultural and Educational Activities of the Belarusian National Organizations in Ukraine in 1918
Keywords: білоруські національні організації; Україна; Білорусь; «Білоруське ехо»; Belarusian national organizations; Ukraine; Belarus; «the Belarusian echo»; «Belarusian club»; «Zorka» Statute